Efektivnost a finanční stabilita investičního projektu - Navrátilík, Pavel (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Práce se zaměřuje na ekonomickou efektivnost a finanční stabilitu investičních projektů. V teoretické části je práce zaměřena na vysvětlení základních pojmů týkajících se investičních projektů a dále se v teoretické části zabývá životní fází projektu, predikcí peněžních toků, metodami hodnocení investic, faktory ovlivňující investiční rozhodování a zdroje financování investičních záměrů. V praktické části dochází k aplikaci teoretických poznatků na reálném investičním projektu a jeho analýzou hledá doporučení pro jeho realizaci.

The Master Thesis focuses on an investment project’s economic effectiveness and stability of financing. In the theoretical part of the thesis there are basic ideas on investment projects explained and further the thesis deals with project lifecycle phases, cash flow predictions, methods of investment economic evaluation, factors that influence investment decision making and sources of project’s financing. In the practical part there are these theoretical findings applied on a real investment project and by analyzing it is searching for a recommendation for a project realization.
Efficiency and Financial Stability of Investment Project
Keywords: Efektivnost; investiční projekt; peněžní toky; financování; vlastní kapitál; cizí kapitál; investiční rozhodnutí; Effectiveness; investment project; cash flow; financing; shareholder's capital; foreign capital; investment decision making